(untitled) (Journal of the College of Education for Women, 2019)
The United States has stood by Iraq and supported militarily and morally, but the relationship did not quickly be strained again before August 1990, when the oldest former political system in Iraq after Iraqi troops entered the territory of Kuwait, the United States stood beside Kuwait because the two parties link military ties opted States United to support the Kuwaiti side relying on the resolutions passed by the UN security Council, the United States and found in this issue right opportunity to execute the mechanics of meddling in Iraqi affairs and the various means of political, economic, military, and methods for dealing with Iraq, especially after finding the impediment standing in front of the implementation of its goals The strategy developed by the end of the cold war over the Arabian Gulf region and throughout the Middle East.Came up in 2003, the United States will implement the last goal of the occupation of Iraqi territory and topple its political system where he gave several reasons for their rationalizations I did this, but in order to take their relations a new turn sought to contain Iraq by linking a number of security and strategic agreements, including the Conventions (the withdrawal of US troops Iraq and the strategic framework Agreement in 2008) and two and promised to drive Iraq from Chapter VII of the UN sanctions and guardianship internationalism full sovereignty and international status and retrieve.The Msaralalaqat US-Iraqi post-election March 72 010 made relations turn towards the broader perspective of cooperation for their work in the framework of strategic interactionwith the Convention on the strategic framework, particularly since the Iraq part of the system’s strategic interests and this is what explains the saying US President Eisenhower (that Iraq was a fortress of stability and peace In the area.)Thus US-Iraqi relations will remain linked to the nature of the political decision-maker of the outside of both sides for their policy to achieve political, economic and security gains to both sides of the equation.